Pengaruh Pendekatan Open-Ended Terhadap Hasil Belajar Siswa Kelas XI MA Darul Ulum Waru - Vicka Nur Rizky; Hanim Faizah (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2020)
This research has the background that there are still many students are still lacking in understanding mathematical concepts in students and its effect on student learning outcomes Class XI MA Darul Ulum. Therefore, it requires an approach that can improve learning outcomes, one of which is the approach Open-ended.The purpose is to determine the effect of the open-ended approach to the learning outcomes of students in grade XI MA Darul Ulum Waru.This research is a quantitative type of research True Experimental design and research design posttest control group design. The sampling technique using simple random sampling technique and obtained samples of the class XI IPA 1 as an experimental class and class XI IPA 2 as the control class with the population of all students in grade XI MA Darul Ulum Waru. The data collection technique using the test, observation methods and techniques of data analysis using t-test. From the analysis of the data obtained 2,35and 1,99 then = 2.35 > 1.99 and the average value of the experimental class is higher than the control class, it can be concluded that there is the effect of the open-ended approach to the learning outcomes of students in grade XI MA Darul Ulum Waru.